Evaluasi Rasio Kapasitas Plat Lantai Jembatan Pangwa Berdasarkan Mutu Beton Aktual - munawir; Auzan, Basil (Tameh, 2024)
This article reviewed the effect of decreasing quality of concrete in the vehicle deck on Pangwa bridge located in Trienggadeng, Pidie Jaya district, Aceh Province. The bridge deck was planned to use concrete with a quality of 30 MPa, however in practice, it was estimated that only 18.8 MPa was achieved. Based on the actual concrete quality, this article reported a reanalysis of the bending and shear capacity ratio. Structural analysis was carried out using SAP2000 software referring to engineering design data. The stages include modeling the bridge as a space frame steel construction with a deck using reinforced concrete material, loads calculation, internal force analysis, and checking the structural capacity. Load calculations and load combinations refer to the standard Loading for Bridges (SNI 1725: 2016). The bridge deck was analyzed as a one way slabs using D16-150 reinforcement with steel grade fy = 320 MPa. The loads taken into structure analysis include: self weight, additional dead load, truck load, and wind load. Based on the loads on the bridge, it is estimated that the possible forces arising from certain conditions are calculated based on the ultimate load combination of Strength-I, Strength-II, Strength-III, Strength-IV and Strength-V according to the provisions of SNI 1725-2016. Based on the results of the structural analysis recapitulated from the value of the load combination, the maximum and minimum moments were 388.68 kN.m and -391.22 kN.m while the maximum shear force were 169.60 kN. The planned bending capacity was 396.303 kN.m (design) and was achieved at 365.568 kN.m (actual) or 7.75% less than the ultimate moment. The pons shear force arising on the bridge deck was Vu = 169.6 kN with pons shear capacity, ØVn = 874.895 kN in the design data and was achieved by 703.811 kN (actual). Based on the results of these calculations, it can be concluded that Pangwa bridge still meets the level of safety for the use as a vehicle traffic lane.